PERBEDAAN JARAK TANAM TERHADAP PRODUKTIVITAS DEFOLIASI PERTAMA RUMPUT MOTT (Pennisetum purpureum cv. Mott - Nur Istikomah; Agustina Widyasworo Kunharjanti (Universitas Islam Balitar, 2017)
The research was conducted in Sumber Sumber Village of Sanankulon District of Blitar, during April 22 to June 16, 2017.The trial used 10 Mott grass poles on each plot with different spacing ie, P0 = 50 x 100 cm, P1 = 75 x 100 cm, P2 = 100 x 100 cm and P3 = 125 x 100 cm. Parameters measured were number of tillers, plant height, leaf length, leaf width, fresh weight and leaf green index. The design used was a complete randomized design (Gazpers, 1991) consisting of 4 treatments of 6 replications.The result of variance showed that the difference of plant spacing had no significant effect (p > 0,05) on productivity including number of tiller, plant height, leaf width, leaf length, fresh weight of green leaf index. Based on the results of research on differences in spacing to the productivity of first defoliation Mott grass then Need further research on the effect of cropping methods on grass growth and productivity.Keywords: plant spacing, Mott grass, productivity.